Isolation of an imino-N-heterocyclic carbene/germanium(0) adduct : a mesoionic germylene equivalent - Su, Bochao (2015)
An autoionization of germanium dichloride/dioxane complex with an imino-N-heterocyclic carbene ligand (L) afforded a novel germyliumylidene ion, [(L)GeCl]+[GeCl3]−, which was fully characterized. Reduction of the germyliumylidene ion with potassium graphite produced a cyclic species [(L)Ge], which can be viewed as both a Ge0 species and a mesoionic germylene. X-ray diffraction analysis and computational studies revealed one of the lone pairs on the Ge atom is involved in the π system on the GeC2N2 five-membered ring. It was also confirmed that the nucleophilic behavior of [(L)Ge] as a two lone-pair donor.